Controle postural estático e dinâmico de mulheres com e sem incontinência urinária - Porolnik, Sinara (2018)
The study aimed to compare the static and dynamic postural control (PC) of women with and without urinary incontinence (UI), for which a cross-sectional study was carried out, where 24 women aged 37-83 years were divided in 2 groups: 12 with UI and 12 with UI. As eligibility criteria, included women over 37 years old, with preserved cognitive ability, evaluated through the Mini Mental State Examination (MMSE), according to their schooling; and with functional independence, evaluated through the Katz Index. All active physically evaluated by the International Physical Activity Questionnaire (IPAQ). Excluding women with neurological pathologies (self-reported), with cognitive deficit less than 24 points assessed by MMSE; with labyrinth disorders; use orthoses or prostheses in upper or lower limbs; amputation of limbs; surgery for the treatment of UI; therapy for UI treatment; and who were on hormone replacement therapy. The work was approved by the Research Ethics Committee of UFSM, all of them signed the Free and Informed Consent Term. For the characterization of the sample, a registration form was used composed of data of identification of the participants, elaborated by the researchers. The International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) was used to characterize urinary losses and define the groups of women with and without UI. Static and dynamic PC (squatting) data were obtained through the force platform, and the variables listed were the anteroposterior displacement range of COP (COPap); medium-lateral displacement range of COP (COPml); the average COP displacement velocity (COPvel) and the ellipse area (AE). Statistical analysis using SPSS 13 software and group representation through descriptive statistics. The Shapiro-Wilk normality test was performed and for the comparison between the groups for the parametric variables Student's t-Test. The analysis of the non-parametric variables was performed using the Mann Whitney U test and the Chi-square test (CHI²) for the categorical variables. The level of significance was 5% for all tests. The effect size established was the "d" of Cohen. There was a difference between the groups in the educational level (p = 0.021), the other variables of the sample characterization did not present a significant difference. In the static PC there was no statistical difference and in the dynamic PC there was a difference between the groups in the AE variable (p = 0.04), the other variables did not present a significant difference. We attempted to identify the size of the effect of the finding, with COPap - effect size of 0.803; and AE - effect size of 0.874, both considered to have great effect; in the other variables the effect size was very small or small. Therefore, women with UI have a dynamic PC impairment, that is, they have a worse PC. Thus, the relationship of the pelvic floor muscles with the balance encompasses the pelvic and abdominal structures that are of paramount importance to maintain PC. Despite the variability of age, this factor was not what influenced the occurrence of UI.